Evaluation of Spreadable Cheese Made with Goat’s Milk and Soymilk in Various Rations - Arief, Muhammad Fajrul; Manab, Abdul; Agustin, Lia (Universitas Brawijaya, 2025)
This study aimed to determine the characteristics of spreadable cheese made from goat milk (GM) and soy milk (SM) in various rations. The ratios of GM and SM were P0 (control), P1 (3:1), P2 (1:1), and P3 (1:3) (v/v), respectively. P0 was the treatment without adding SM. This study was conducted using a completely randomized design with 4 replications. All data were processed using ANOVA and DMRT. The results showed that the combination of milk reduced saturated fatty acids, which affected the levels of water, fat, casein, and calcium (p < 0.05), but not significantly on salt, protein, and pH levels. The sensory quality assessment was observed using a hedonic test and expressed in histogram form. To conclude, spreadable cheese produced from various rations of GM and SM has sufficient flavor-creamy, as well as good spreadability and color.